2022
DOI: 10.3390/life12111736
|View full text |Cite
|
Sign up to set email alerts
|

Light in the Rational Treatment of Autism? Effects of Metformin on Steroid Hormones in a Patient with Polycystic Ovarian Syndrome (PCOS)

Abstract: Background. Metformin is an effective treatment option for type 2 diabetes mellitus, and it is, to this day, the most prescribed oral antiglycaemic drug. Besides its effects mainly on mitochondrial activity, an off-label use came up as a pharmaceutical for subjects with a diagnosis of polycystic ovarian syndrome (PCOS) along with altered steroid hormone homeostasis. Besides these effects, even an influence on mood and social behavior was described, leading to the aim of this case report to elucidate the effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It was previously reported that metformin had serious effects on steroid hormone levels [ 10 ]. We found that enzymatic activities were partly altered after the metformin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was previously reported that metformin had serious effects on steroid hormone levels [ 10 ]. We found that enzymatic activities were partly altered after the metformin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid hormones mediate many cascades in the human body [ 10 ] ( Figure 1 ); the dysregulation of these was identified in conditions such as high blood pressure, Cushing’s syndrome, post-traumatic stress disorders, depression and even autism [ 11 , 12 ]. Therefore, enzymes play a crucial role in targeting prenatal androgren exposure, such as aromatase or CYP17A1, and appear to influence mental health [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation